Automatic Symbolic Polynomial Operations - Pookaiyaudom, S.; Kuhanont, T. (My University, 1977)
A method of automatic symbolic polynomial operations is described, which is directly applicable to the Rayleigh and Ritz variational method, and is also suitable for obtaining analytic symbolic solutions to large network analysis problems. Copyright © 1977 by The Institute of Electrical and Electronics Engineers, Inc.